PELATIHAN PENGEMBANGAN SOAL MODEL ASESMEN HIGH ORDER THINKING SKILLS (HOTS) UNTUK GURU GUGUS 8 KKG SD LUBUKLINGGAU TIMUR II KOTA LUBUKLINGGAU - Akmal Rijal; Tio Gusti Satria (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
The emphasis of the 2013 curriculum is to make students or students have better abilities in observing, asking, reasoning, and communicating. Questions developed using three higher order thinking categories based on Bloom's taxonomic revision, namely, analyzing, evaluating, and creating, where each level has its own criteria which can be adopted into the problem and the objectives of the learning to be achieved. Based on the results of the identification of partners found problems teachers still have difficulty in making questions that are able to encourage students to develop higher-order thinking skills (HOTS) and have not made students want to analyze the questions before answering, the teacher gives practice questions or test questions to students only fixated on the category remember, understand, and apply, and facilities and require additional questions for students who have the ability to think at a high level so students are able to develop their way of reasoning. Conduct training and mentoring community service activities using lecture, question and answer, discussion, assignment, project-based methods. The implementation of the PKM training on the development of the High Order Thinking Skills (HOTS) assessment model for the 8th teacher group in the East Lubuklinggau II KKG elementary school went well and the participants were very enthusiastic in participating in the training. The activity has an impact on improving the skills of model development training (HOTS) for teachers in the 8th KKG group at SD Lubuklinggau Timur II, Lubuklinggau City. Keywords: training, questions, HOTS, KKG, elementary school, Lubuklinggau.